2020
DOI: 10.7759/cureus.7066
|View full text |Cite
|
Sign up to set email alerts
|

Cementing Osseointegration Implants Results in Loosening: Case Report and Review of Literature

Abstract: Skeletal transcutaneous osseointegration was performed on a 54-year-old female transfemoral amputee. None of the available osseointegration implants achieved press-fit stability, so an implant was cemented in position. Although initially stable, by six months the patient reported painful loading and radiographs revealed cement mantle lucency. The osseointegration implant was removed, antibiotics were delivered via implanted spacer and intravenously, and revision osseointegration three months later achieved app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Template and choose an implant with an optimal diameter that encroaches the inner cortex at the narrowest bone diameter; an implant that is too wide may not fit without causing a large fracture, and an implant that is too narrow may fall out. Do not cement the implant 7 .Ideally, the abutment of the implant should rest against a flat transverse bone end with cortical contact and leave the correct amount of room for the prosthetic knee so that it matches the height of the contralateral knee; avoid inserting an implant too distally or in too wide a metaphyseal flare.Gentle impaction pressure is necessary and small contained distal fractures are acceptable, but avoid causing a propagating fracture. Do not place cerclage cables or loose bone graft at these small fracture sites.Avoid the use of a tourniquet during intramedullary reaming to prevent potential heat-induced osteonecrosis.Nerve surgery such as targeted muscle reinnervation, if indicated, can be performed in the same surgical episode as the osseointegration.The muscles should be closed at the bone-implant interface with use of a tight purse string in order to provide a vascularized tissue barrier against bacterial ingress 8 .The skin surrounding the stoma should have unnecessary fat removed, but not excess removal leading to skin necrosis.…”
Section: Important Tipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Template and choose an implant with an optimal diameter that encroaches the inner cortex at the narrowest bone diameter; an implant that is too wide may not fit without causing a large fracture, and an implant that is too narrow may fall out. Do not cement the implant 7 .Ideally, the abutment of the implant should rest against a flat transverse bone end with cortical contact and leave the correct amount of room for the prosthetic knee so that it matches the height of the contralateral knee; avoid inserting an implant too distally or in too wide a metaphyseal flare.Gentle impaction pressure is necessary and small contained distal fractures are acceptable, but avoid causing a propagating fracture. Do not place cerclage cables or loose bone graft at these small fracture sites.Avoid the use of a tourniquet during intramedullary reaming to prevent potential heat-induced osteonecrosis.Nerve surgery such as targeted muscle reinnervation, if indicated, can be performed in the same surgical episode as the osseointegration.The muscles should be closed at the bone-implant interface with use of a tight purse string in order to provide a vascularized tissue barrier against bacterial ingress 8 .The skin surrounding the stoma should have unnecessary fat removed, but not excess removal leading to skin necrosis.…”
Section: Important Tipsmentioning
confidence: 99%
“… Template and choose an implant with an optimal diameter that encroaches the inner cortex at the narrowest bone diameter; an implant that is too wide may not fit without causing a large fracture, and an implant that is too narrow may fall out. Do not cement the implant 7 . Ideally, the abutment of the implant should rest against a flat transverse bone end with cortical contact and leave the correct amount of room for the prosthetic knee so that it matches the height of the contralateral knee; avoid inserting an implant too distally or in too wide a metaphyseal flare.…”
Section: Important Tipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because recent literature recognizes TOFA is safe and effective, and the United States Food and Drug Administration (FDA) has approved one implant design [ 12 ], broader use and innovation is expected. Preventing future problems by considering prior knowledge is essential [ 13 , 14 ]. By providing a consolidated summary of the basic science and early clinical experiments preceding and facilitating modern TOFA, it is hoped that this article can help avoid preventable future problems.…”
Section: Introductionmentioning
confidence: 99%
“…Cementing transcutaneous osseointegration implants is an obvious example: as Mooney et al 9 , 10 reported in the 1970s, this approach fails; when ITAP trials confirmed this, the failure data were withheld, 33 leading to a third generation committing the same error. 40 Awareness of and access to foundational knowledge, along with timely reporting of newly discovered problematic situations, could have prevented this patient’s and potentially future patients’ morbidity, because it is patients — not the surgeons or implant companies — who suffer the consequences of poor clinical outcomes. Recounting lessons is better than recalling implants.…”
mentioning
confidence: 99%